Antimalarial efficacy and toxicological assessment of medicinal plant ingredients of Prabchompoothaweep remedy as a candidate for antimalarial drug development - Chaniad P. (2023)
Background: Drug resistance exists in almost all antimalarial drugs currently in use, leading to an urgent need to identify new antimalarial drugs. Medicinal plant use is an alternative approach to antimalarial chemotherapy. This study aimed to explore potent medicinal plants from Prabchompoothaweep remedy for antimalarial drug development. Methods: Forty-eight crude extracts from Prabchompoothaweep remedy and its 23 plants ingredients were investigated in vitro for antimalarial properties using Plasmodium lactate dehydrogenase (pLDH) enzyme against Plasmodium falciparum K1 strain and toxicity effects were evaluated in Vero cells. The plant with promising antimalarial activity was further investigated using gas chromatography-mass spectrometry (GC-MS) to identify phytochemicals. Antimalarial activity in mice was evaluated using a four-day suppressive test against Plasmodium berghei ANKA at dose of 200, 400, and 600 mg/kg body weight, and acute toxicity was analyzed. Results: Of the 48 crude extracts, 13 (27.08%) showed high antimalarial activity against the K1 strain of P. falciparum (IC50 < 10 μg/ml) and 9 extracts (18.75%) were moderately active (IC50 = 11–50 μg/ml). Additionally, the ethanolic extract of Prabchompoothaweep remedy showed moderate antimalarial activity against the K1 strain of P. falciparum (IC50 = 14.13 μg/ml). Based on in vitro antimalarial and toxicity results, antimalarial activity of the aqueous fruit extract of Terminalia arjuna (IC50 = 4.05 μg/ml and CC50 = 219.6 μg/ml) was further studied in mice. GC-MS analysis of T. arjuna extract identified 22 compounds. The most abundant compounds were pyrogallol, gallic acid, shikimic acid, oleamide, 5-hydroxymethylfurfural, 1,1-diethoxy-ethane, quinic acid, and furfural. Analysis of the four-day suppressive test indicated that T. arjuna extract at dose of 200, 400, and 600 mg/kg body weight significantly suppressed the Plasmodium parasites by 28.33, 45.77, and 67.95%, respectively. In the acute toxicity study, T. arjuna extract was non-toxic at 2000 mg/kg body weight. Conclusions: The aqueous fruit extract of T. arjuna exerts antimalarial activity against Plasmodium parasites found in humans (P. falciparum K1) and mice (P. berghei ANKA). Acute toxicity studies showed that T. arjuna extract did not show any lethality or adverse effects up to a dose of 2000 mg/kg.